Effects of the FITKids physical activity randomized controlled trial on conflict monitoring in youth. (4th October 2017) - Drollette, Eric S.; Pontifex, Matthew B.; Raine, Lauren B.; Scudder, Mark R.; Moore, R. Davis; Kao, Shih‐Chun; Westfall, Daniel R.; Wu, Chien‐Ting; Kamijo, Keita; Castelli, Darla M.; Khan, Naiman A.; Kramer, Arthur F.; et al.
Abstract: The present study investigated the effect of a 9‐month physical activity (PA) intervention on children's cardiorespiratory fitness levels and neuroelectric indices of conflict monitoring (i.e., error‐related negativity, ERN). Four hundred twenty‐eight preadolescent children (8–9 years old) were randomized into a PA intervention or wait‐list control group, and completed a fitness and cognitive control assessment (i.e., modified flanker task) at pre‐ and posttest. Following exclusion criterion, 308 children were included in the analyses (PA intervention: n  = 139; wait‐list control: n  = 169). Children in the intervention displayed greater improvements in fitness and response accuracy, which were accompanied by stability of ERN amplitude from pre‐ to posttest. In contrast, the control group revealed increased ERN amplitude at posttest compared to pretest, despite no change in fitness or task performance. These findings demonstrate the efficacy of daily PA for promoting children's fitness and underlying neural processes associated with effective conflict monitoring. Such findings have significant implications for promoting organized PA programs intended to foster overall physical and brain health in school age children.